Marketing Mix Elementa Effect on Egyptian Consumers Buying Behavior for Cosmetics - Eshra, Nevine; Beshir, Noha (Archives of Business Research, 2022)
Cosmetics play vital roles and have an impact on consumers everyday survives on constructing one self-esteem and confidence. Young consumers have become beauty aware and charming in the beauty lifestyle. Demand for cosmetics is dynamic in Egypt but, less consideration keen to the cosmetic industry in the literature. One main issue faced by marketers is their changing behavior, tastes, and preferences. Marketers are trying to deal with their behavioral changes and understanding their decision-making factors correctly and accurately. Therefore, the study purposes to examine the impact of product, price, promotion, and place on buying behavior of Egyptian consumers of makeups. The research is a descriptive research, with the survey conducted through questionnaire. The sampling technique used was convenience, with 120 samples achieved. The empirical results confirm that marketing mix elements overall have positive relationship with consumer buying behavior for makeup in Egypt. Also, price is the only marketing mix element that have significant positive impact on consumer buying behavior for makeup in Egypt.